Perbedaan Kadar Kolesterol Total Metode CHOD-PAP Dalam Sampel Serum Segera Dan Ditunda Selama 2, 4, 6 Jam Pada Suhu Ruang - Pratiwi, Isnaini Nisa Restu; Susanti, Ellis; Fauziah, Prima Nanda; Latifah, Imas; Masdianto (Universitas Mohammad Husni Thamrin, 2025)
Cholesterol examination is important to monitor the presence or absence of abnormalities in fat metabolism characterized by an increase or decrease in fat, the sample used for cholesterol examination is fresh serum and immediately examined. This study aims to determine the difference in total cholesterol levels CHOD-PAP method in serum samples immediately and delayed for 2, 4, 6 hours at room temperature. This research uses experimental designs with a cross sectional design which is tested on 40 samples of Regular Students of Semester 6 of the DIII Medical Laboratory Technology Study Program at Mohammad Husni Thamrin University. The sample examination method is done by taking venous blood and processed into serum. Research results that have been statistically tested on the Friedman test can be concluded for serum samples immediately and delayed for 2, 4, 6 hours with a significant value of 0.711> α (0.05), there is no difference in the results of the examination of total cholesterol levels with immediate work and a delay of 2, 4, 6 hours. In the percentage test, it was concluded that there was a decrease in the results of checking cholesterol levels in serum samples delayed 2, 4 hours by 2.9% and 5.7% in serum samples delayed 6 hours. Total cholesterol examination should be carried out immediately without delay. If the examination is delayed, the storage temperature and how long the delay should be considered. Keywords: CHOD-PAP, Cholesterol, Serum, Delay Time